Outcomes of a multidisciplinary transition clinic for youth with type 1 diabetes. Issue 1 (23rd December 2022) - Wongyai, Wariya; Boonchaya‐anant, Patchaya; Laichuthai, Nitchakarn; Aroonparkmongkol, Suphab; Veerapong, Varaporn; Leepulsup, Suwaputr; Teeratongdee, Chantaporn; Anunapibut, Nuntawan; Sahakitrungruang, Taninee
Abstract: Background: Emerging adults with type 1 diabetes (T1D) have several challenges regarding diabetes management and care transition from pediatric to adult services. In this study we aimed to assess the effectiveness of the newly established transition clinic for emerging adults with T1D. Methods: We conducted an observational study of emerging adults with T1D treated in a transition clinic jointly operated by a pediatric and adult multidisciplinary care team during 2019–2021. A retrospective chart review of hemoglobin A1c (HbA1c), frequency of clinic attendance, acute diabetes‐related complications, assessment of gaps in knowledge and behavior, and psychosocial outcomes was analyzed. Results: A total of 21 patients with T1D were included. Median age at the transfer to the transition clinic was 24 years (range 21–34). Fifteen patients (71%) were successfully transferred to adult services; mean duration of follow‐up at the transition clinic was 9.2 months (SD 3.9). None of the patients was lost to follow‐up or experienced serious diabetes related complications. Mean (95% confidence interval) HbA1c levels decreased from 8.97% (7.87–10.07) at baseline to 8.25% (7.45–9.05) at the most recent visit ( p = 0.01). A proportion of patients achieving the glycemic target (HbA1c < 7.5%) was increased from 24% at the first visit to 38% at the most recent visits. Patients' HbA1c levels at the adult clinic continued a favorable trend. Seven patients (33%) were identified as having symptoms of depression. Knowledge and behavioral gaps were identified and counselled by clinical care team. Conclusion: The multidisciplinary transition clinic has shown to be beneficial in terms of improving glycemic control, maintaining continuity of care and clinic attendance.